High testosterone levels associated with elevated suicidal risk in male adolescents with depression - Han Wang; Nan Lyu; Juan Huang; Bingbing Fu; Lili Shang; Fan Yang; Ling Zhang; Qian Zhao (BMC Psychiatry)
Abstract Background Adolescent suicide, as a public health issue, is becoming increasingly urgent, yet there remains a lack of effective objective biomarkers for identifying high-risk adolescents. While testosterone has been linked to suicide, no definitive conclusions have been reached. Studies in specific populations defined by significant changes in age or hormone levels and by gender have shown greater reproducibility. This study aims to investigate the association between testosterone levels and suicidal ideation or behavior in male and female adolescents with major depressive disorder (MDD). Methods This retrospective, cross-sectional study included 1227 adolescents with MDD, aged 10–19 years, hospitalized at the Beijing Anding Hospital, Capital Medical University, from January 2013 to December 2020. Patients were categorized into two groups: those with suicidal ideation or behavior (MDS) and those without (MDNS). Demographic data, clinical characteristics, and serum testosterone levels at admission were extracted and compared. An additional 579 adolescents meeting the same inclusion criteria were included for validation, with data collected from January 2022 to December 2023. Results In male adolescents, testosterone levels were significantly higher in the MDS group compared to the MDNS group(Z = -4.340, P < 0.001). After adjusting for confounding factors, testosterone levels remained significantly associated with suicidal ideation or behavior (OR = 1.220, 95% CI: 1.098–1.356). This finding was confirmed in the validation data set (OR = 1.444, 95% CI: 1.139–1.832). No significant difference in testosterone levels was observed in females (Z = 1.643, P = 0.100). Conclusions Elevated serum testosterone levels were independently associated with increased risk of suicidal ideation or behavior in male adolescents with MDD, but not in females. These findings highlight the necessity for sex-specific biomarkers, however, due to the intrinsic limitations of the current study, they necessitate further validation. Clinical trial number Not applicable.